2018
DOI: 10.1159/000491071
|View full text |Cite
|
Sign up to set email alerts
|

PLAUR Confers Resistance to Gefitinib Through EGFR/P-AKT/Survivin Signaling Pathway

Abstract: Background/Aims: Tyrosine kinase inhibitor gefitinib significantly improves the survival of patients with non-small-cell lung cancer (NSCLC) by inhibiting epidermal growth factor receptor (EGFR) tyrosine kinase. However, patients eventually develop resistance to gefitinib through uncharacterized mechanisms. It is known that plasminogen activator urokinase receptor (PLAUR) plays an important role in cell proliferation, migration and apoptosis. However, the role of PLAUR, particularly exosomal PLAUR in gefitinib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 59 publications
1
34
0
Order By: Relevance
“…Moreover, as reported by Liu et al, GLS2 negatively regulates the PI3K/AKT signaling pathway [32]. It has been widely known that, when uPAR is expressed at low levels, pAkt is downregulated [33] while pERK is strongly upregulated; uPAR loss, in fact, inhibits the PI3K/Akt pathway and forces the cells to use ERK as an alternative pathway to grow and survive [34]. Here, we verified this mechanism reporting that after uPAR loss, the phosphorylation of Akt was inhibited and, to compensate for this effect to keep the cell proliferating and surviving, the phosphorylation levels of ERK were enhanced.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, as reported by Liu et al, GLS2 negatively regulates the PI3K/AKT signaling pathway [32]. It has been widely known that, when uPAR is expressed at low levels, pAkt is downregulated [33] while pERK is strongly upregulated; uPAR loss, in fact, inhibits the PI3K/Akt pathway and forces the cells to use ERK as an alternative pathway to grow and survive [34]. Here, we verified this mechanism reporting that after uPAR loss, the phosphorylation of Akt was inhibited and, to compensate for this effect to keep the cell proliferating and surviving, the phosphorylation levels of ERK were enhanced.…”
Section: Discussionmentioning
confidence: 76%
“…In previous studies, we have demonstrated the feasibility of measuring miRNA or mRNA in EVs ( 13 , 14 ). In this study, we developed an HNCIB system and show that the system is capable of highly efficient capture of EVs and simultaneous detection of proteins and RNA in a single EV.…”
Section: Resultsmentioning
confidence: 99%
“…1a, b). To further understand the mechanism of gefitinib resistance, we generated gefitinib-resistant PC9R cells by exposing gefitinib-sensitive PC9 cells to increasing concentrations of gefitinib [39]. We found that in the gefitinib-resistant PC9R cells, GK5 was significant upregulated compared to that in gefitinib-sensitive PC9 by quantitative reverse transcription qRT-PCR and Western blotting analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The human lung adenocarcinoma cell line PC9 and NCI-H1975 (H1975, intrinsically harbor EGFR L858R/T790 M) were purchased from the American Type Culture Collection (ATCC, Rockville, MD, USA). To induce gefitinib resistance, PC9 cells were exposed to increasing concentrations of gefitinib [39]. The gefitinib-sensitive PC9 and -resistance PC9R and H1975 cells were cultured in RPMI 1640 medium (Thermo Fisher Scientific, MA, USA) supplemented with 10% heat-inactivated fetal bovine serum and 100 U/ml penicillin/streptomycin.…”
Section: Methodsmentioning
confidence: 99%